IDENTIFIKASI KEMAMPUAN LITERASI MATEMATIKA SISWA SMP NEGERI 12 JEMBER DALAM MENYELESAIKAN SOAL PISA KONTEN SPACE AND SHAPE - Fiad, Uluf; Suharto, Suharto; Kurniati, Dian (Kadikma, 2017)
Abstract. The research is research descriptive qualitative aimed at described the ability literasi in about pisa to their students age of 15 .This research use of the instruments tests the ability of literasi in about pisa that have been translated in indonesian language .Data collection method used in research that is a method of tests .This study did not use the sample collection , but by identifying all subject based on indicators the ability literasi according to pisa for the purpose identify of the ability of literasi mathematics .From the data analysis , obtained the conclusion that students reached indicator to 3 students able to perform the procedure clearly , including procedures that requires decision respectively , is able to solve problems , apply a strategy simple , capable of interpret and use representation based on a source of information different and said the reasons in direct. Keywords: The ability literasi mathematics , about pisa content space and shape